Fect of nickel induced biochemical alterations in fresh water bivalve, lammellidens marginalis - Andhale, A V; Zambare, S P (Journal of Ecobiotechnology, 2012)
This study done with the observations of biochemical changes in bimolecular contents of, DNA, RNA, protein and collagenÂ  after chronic exposure (at 15 and 30days) to nickel chloride (0.227ppm, equivalent to the LC50/10 of 96 hours exposure) from various tissues such as gill, foot, digestive gland and whole body of control and experimental bivalves, Lamellidens mrginalis. It was observed that protein, collagen, DNA and RNA were dramatically decreased in treated bivalves as compeered to controlled bivalves.